Baseline Functional Mobility in Hospitalized Persons With Anorexia Nervosa: A Retrospective Study of Inpatient Physical Therapy During Medical Stabilization. Issue 1 (January 2017) - Laging, Michelle A.; Brinton, John T.; Sabel, Allison L.; Gaudiani, Jennifer L.; Mehler, Philip S.
Abstract : Purpose: This study evaluates potential associations of baseline physical function measures with anthropometrics and clinical outcomes in persons hospitalized with anorexia nervosa. Methods: We conducted a retrospective study in a single hospital on 176 seriously ill persons with anorexia nervosa who required definitive medical stabilization. Licensed physical therapists assessed functional transfers and ambulation using the Functional Independence Measure. Walking speed, Tinetti Performance-Oriented Mobility Assessment, demographic, and anthropometric measures were also collected. Results: Ninety-one percent of the participants were female (N = 161), with a median age of 28 years (interquartile range, 22-39) and mean body mass index upon admission of 12.7 kg/m 2 (standard deviation, 1.8). Significant positive correlations were observed between all 3 in-room measures of physical function and admission weight, percent ideal body weight, and body mass index (all P < .02). Age was inversely correlated with ambulation per the FIM score ( r =−0.15; P = .05). After adjusting for age and admission weight, in-room physical function measures were inversely associated only with length of hospitalization ( R 2 = 0.30). For every 1.0-unit increase in bed mobility, the length of hospitalization decreased by 2.9 days (95% confidence interval, −5.0 to −0.8). Conclusion: A sizable proportion demonstrated modified dependence, or required assistance, in functional mobility skills. Lower initial bed mobility scores are associated with longer hospitalization.